'Mammy's supposed to be strong and supportive – not sitting in a corner rocking and crying': an interpretative phenomenological analysis of British mothers' experiences of postnatal depression. (4th May 2022) - Khalid, Farah; Hirst-Winthrop, Sarah
ABSTRACT: Objective: To gain an in-depth understanding of the lived experience of women with postnatal depression (PND). Background: Although there is a small body of existing research which explores subjective experience of this phenomenon, relatively little research has been carried out and is prior to the publication of the NICE guidelines for PND in 2007. Method: Semi-structured interviews were carried out with six mothers (aged 23–40 years), who had taken part in a PND support group. Verbatim transcripts were analysed using Interpretative Phenomenological Analysis (IPA). Results: One broad superordinate theme of 'the conflicted mother' emerged from the data, with four corresponding sub-themes (own mother as absent and judgemental; internalised mother; pregnancy on the road to motherhood as an unpleasant stranger; the ideal mother). Conclusion: It is argued that a broad umbrella construct of 'the conflicted mother' exists in PND experience. This study highlights the importance of the mother's own maternal relationship in living with depression. The authors discuss limitations of the study, make service recommendations to improve current clinical practice for women with PND, and provide future research directions.